STRENGTH OF GLASS FIBRE REINFORCED POLYMER (GFRP) GRATING AFTER AGEING FOR OFFSHORE STRUCTURE APPLICATION - HABIB, AMIR IZZUDDIN HASANI (2015)
The main disadvantages ofsteel for offshore application are its corrosion properties and heavy weight for transportation. Glass Fibre Reinforced Polymer (GFRP) material has been given the attention to replace steel in offshore platform due to its non-corrosive characteristic and good low weight to strength ratio. The grating made ofGFRP is being considered to replace the existing steel gratmg for walkways on the offshore platforms. However, there is no available data on the long term strength performance ofthe GFRP grating behaviour. One way of studying the long term strength performance of GFRP material is by using accelerated ageing method. Immersion of GFRP materials in variation type of solution at elevated temperature is among the accepted accelerated ageing method along with the use Arrhenius model principle to predict the long term strength performance of GFRP materials.